ESP32 charging system prototype for EV: Design and implementation using wireless energy transmission - Sallem Amin; Souissi Zied; Nasri Mohamed Aziz; Benhala Bachir; Masmoudi Nouri (E3S Web of Conferences)
Electric vehicles (EVs) are gaining popularity due to their cost-effectiveness and environmental advantages. The major objective is to design charging systems that can support extended vehicle usage. The current charging infrastructure relies on conductive ways, but technological advancements are offering wireless options. Inductive EV charging, a wireless alternative, eliminates the need for physical cables and runs on solar energy, hence removing the requirement for external power sources. This novel technology recharges EVs while they are in motion, removing the need for refueling. Batteries, transformers, solar panels, copper coils, regulator circuits, ESP32 controllers, AC / DC converters are among the prototype design components.